2021
DOI: 10.1002/mco2.56
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 infection in patients with connective tissue disease: A multicity study in Hubei province, China

Abstract: Novel Coronavirus disease 2019 (COVID‐19) has spread rapidly around the world. Individuals with immune dysregulation and/or on immunosuppressive therapy, such as rheumatic patients, are considered at greater risk for infections. However, the risks of patients with each subcategory of rheumatic diseases have not been reported. Here, we identified 100 rheumatic patients from 18,786 COVID‐19 patients hospitalized in 23 centers affiliated to Hubei COVID‐19 Rheumatology Alliance between January 1 and April 1, 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…The main presenting symptoms in the HCQ group were cough in 45 patients (84.9%) and fever in 38 patients (71.7%), while cough was the main presenting symptom in the second group (75.6 %). These findings are in line with the findings of studies by Ye et al 2021 (11) and Pham et al 2021 (15) which showed that fever and cough were the most common symptoms in both groups of their studies. Rhinorrhea was significantly presented among 2nd group cases (P=0.015), this finding is similar to what was reported by Pham et al 2021 (15) in their study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The main presenting symptoms in the HCQ group were cough in 45 patients (84.9%) and fever in 38 patients (71.7%), while cough was the main presenting symptom in the second group (75.6 %). These findings are in line with the findings of studies by Ye et al 2021 (11) and Pham et al 2021 (15) which showed that fever and cough were the most common symptoms in both groups of their studies. Rhinorrhea was significantly presented among 2nd group cases (P=0.015), this finding is similar to what was reported by Pham et al 2021 (15) in their study.…”
Section: Discussionsupporting
confidence: 92%
“…Infection with COVID-19 might be very extensive in cases with CTD. Despite the lower possibility of severe COVID-19 infections in patients receiving HCQ and/or glucocorticoid therapy with lowto medium-dose, immunosuppressive agents should be used with extra caution due to their dysregulated immune response (11) .…”
Section: Introductionmentioning
confidence: 99%
“…In line with these results, treatment with higher dosages of GC in patients with rheumatic diseases has been shown as an independent risk factor associated with COVID-19-related death [41,42]. In contrast again, there are studies that do not see any significant correlation in multivariable adjusted analyses [43], or even one report that suggests reduced disease progression from mild to critical conditions under low-to medium-dose GC treatment (5-15 mg/day prednisone) [44]. However, the latter study consisted of only 22 patients with GC therapy.…”
Section: Risk In Exogenous Glucocorticoid Excessmentioning
confidence: 74%
“…It is well accepted that COVID-19 patients with comorbidities are potentially very high risk for death if they progress to oxygen desaturation and are hospitalized for complications of COVID-19. [ 11 12 13 ] However, the mortality rate of the patients under the review was surprisingly low even in the very limited health care setting. Moreover, 90% of our patients were unvaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, high mortality rate was seen in the patients with age more than 60 years, diabetes, hypertension, cardiovascular diseases (CVD), chronic respiratory diseases including asthma and chronic obstructive disease (COPD), HIV, connective tissue disorders and hence they are high-risk groups for severe COVID-19 disease. [ 11 12 13 ] It would be more rational to consider remdesivir initiation among the high-risk COVID-19 patients during viral phase.…”
Section: Introductionmentioning
confidence: 99%